Local Character Values in Remo Dance Extracurricular Activities: Efforts to Cultivate Cultural Appreciation in Primary School Students - Tupriya; Puspita, Ari Metalin Ika; Istiq'faroh, Nurul; Purwoko, Budi (Journal of Innovation and Research in Primary Education, 2025)
This qualitative descriptive study aims to explore the embodiment of local character values through Remo dance extracurricular activities at SDN Wonokusumo I/40 Surabaya. As a traditional East Javanese dance rich in philosophical and cultural elements, Remo dance serves as an effective pedagogical tool for character education at the primary level. Data were obtained through observation, interviews, and documentation, involving school principals, dance teachers, coaches, and students as key informants. The study applied triangulation of sources and techniques to ensure data validity and reliability. The findings indicate that Remo dance extracurricular activities significantly contribute to the development of students’ character values, including discipline, responsibility, self-confidence, cooperation, and cultural appreciation. Students actively engaged in the learning process demonstrated not only technical mastery of the dance but also internalized moral and social values inherent in the practice. Participation in dance practices and public performances fostered emotional expression, respect for tradition, and a sense of collective pride among learners. Furthermore, the study reveals that the integration of local cultural content through extracurricular activities enhances contextual learning, aligns with the Merdeka Curriculum, and supports national education goals in Indonesia. Despite challenges such as limited resources and time constraints, the commitment of educators and students sustained the continuity and quality of the program. This research highlights the relevance of utilizing traditional arts like Remo dance in educational settings as a culturally responsive approach to character building. It encourages schools to incorporate local wisdom in extracurricular activities to strengthen students’ identity and national cultural values. The study recommends expanding similar programs in other schools to promote cultural sustainability and character development holistically.